Ore Mineralization Characteristics in Hydrothermal Alteration at Mangunharjo and Surrounding Areas, Pacitan, Indonesia - Abdul Faisal Baba; Sri Mulyaningsih; Radhitya Adzan Hidayah (Badan Riset dan Inovasi Nasional, 2022)
The research area is located in Mangunharjo-Grindulu, Pacitan (Indonesia), as part of the Southern Mountain Tertiary Volcanic Arch. Outcrops of quartz veins-riched volcanic rock associated with sulfide minerals are found in this area. The Southern Mountain Oligo-Miocene magmatic arc is known as the potential area that contains precious metal deposits. The study aimed to determine the characteristics of the mineralized zone in this area. The research methods are geological surface mapping, thin-section observation, mineragraphy, and X-Ray Diffraction (XRD). The results show that the constituent lithologies were andesitic lava, breccia, and tuff; co-ignimbrite breccia, dacitic pumice and tuff, and dacitic dike; and pyroxene-rich andesitic volcanic rocks. The geological structure is dominated by oblique normal faults, strike-slip faults, and upward oblique faults associated with shear joints filled with quartz veins. Fieldwork observation, thin-section analyses, and mineragraphic and XRD observations identify three alteration zones in the hydrothermal system: the advanced argillic zone, the intermediate argillic zone, and the chloritized zone. By the mineral’s association, it is interpreted that the advanced argillic zone was formed at a temperature of 220-330oC and pH 3-6 due to dissemination with side rocks located near the hydrothermal flows; the intermediate argillic zone and the chloritized zone were formed at a temperature of 150-300oC and a pH of 5-6 due to chloritized alteration of the hydrothermal fluid carrying the ore. This alteration zone has no economic potential for precious metal minerals so it is better to be developed for education, conservation, and natural laboratories.